2008
DOI: 10.1002/hep.22364
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel immunohistochemical tumor markers for primary hepatocellular carcinoma; clathrin heavy chain and formiminotransferase cyclodeaminase

Abstract: Early diagnosis of hepatocellular carcinoma (HCC) greatly improves its prognosis. However, the distinction between benign and malignant tumors is often difficult, and novel immunohistochemical markers are necessary. Using agarose two-dimensional fluorescence difference gel electrophoresis, we analyzed HCC tissues from 10 patients. The fluorescence volumes of 48 spots increased and 79 spots decreased in tumor tissues compared with adjacent nontumor tissue, and 83 proteins were identified by mass spectrometry. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 44 publications
(45 reference statements)
4
55
0
Order By: Relevance
“…The result supports our hypothesis that COP35 is internalized via clathrin-mediated endocytosis. It was also suggested that CHC is upregulated in hepatocellular carcinoma tissues (30). Consistent with this, our data suggest that CHC expression in CCA lesions was higher than that in normal bile duct epithelium by immunohistochemical staining of formalin-fixed and paraffin-embedded tissues (Table 1; Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The result supports our hypothesis that COP35 is internalized via clathrin-mediated endocytosis. It was also suggested that CHC is upregulated in hepatocellular carcinoma tissues (30). Consistent with this, our data suggest that CHC expression in CCA lesions was higher than that in normal bile duct epithelium by immunohistochemical staining of formalin-fixed and paraffin-embedded tissues (Table 1; Fig.…”
Section: Discussionsupporting
confidence: 88%
“…One was GeLC-MS (18)(19)(20) ). The minimum criteria for protein identification were protein and peptide thresholds set to 95.0% (Scaffold's probability threshold filter) and number of unique peptides set to 2.…”
Section: Fir Binding Protein Identificationmentioning
confidence: 99%
“…Unfortunately genes which prove useful in expression studies not always can be translated in robust tissue markers and used in the routine practice as immunocytochemical tools. We believe our panel susceptible to be improved by the addition of novel markers [11,23] as to further increase the reliability and objectivity of HCC diagnosis in liver biopsies and cytological specimens and to meet the growing expectancy of liver clinicians, surgeons and oncologists.…”
Section: Lrnmentioning
confidence: 99%